Genome-Wide Identification and Characterization of the Aquaporin Gene Family and Transcriptional Responses to Boron Deficiency in Brassica napus - Yuan, Dan; Li, Wei; Hua, Yingpeng; King, Graham J.; Xu, Fangsen; Shi, Lei (Frontiers in Plant Science, 2017)
Aquaporins (AQPs) are an abundant protein family and play important roles to facilitate small neutral molecule transport across membranes. Oilseed rape (Brassica napus L.) is an important oil crop in China and elsewhere in the world, and is very sensitive to low boron (B) stress. Several AQP family genes have been reported to be involved in B transport across plasma membranes in plants. In this study, a total of 121 full-length AQPs were identified and characterized in B. napus (AC genome), and could be classified into four sub-families, including 43 PIPs (plasma membrane intrinsic proteins), 35 TIPs (tonoplast intrinsic proteins), 32 NIPs (NOD26-like intrinsic proteins), and 11 SIPs (small basic intrinsic proteins). The gene characteristics of BnaAQPs were similar to those of BraAQPs (A genome) and BolAQPs (C genome) including the composition of each sub-family, gene structure, and substrate selectivity filters. The BnaNIP was the most complex AQP sub-family, reflecting the composition of substrate selectivity filter structures which affect the permeation of solution molecules. In this study, the seedlings of both B-efficient (QY10) and B-inefficient (W10) cultivars were treated with two boron (B) levels: deficient (0.25 μM B) and sufficient (25 μM B). The transcription of AQP genes in root (R), juvenile leaf (JL), and old leaf (OL) tissues of both cultivars was investigated under B deficient and sufficient conditions. Transcription of most BnaPIPs and BnaTIPs was significantly increased compared with other BnaAQPs in all the three tissues, especially in the roots, of both B-efficient and B-inefficient cultivars under both B conditions. With B deprivation, the expression of the majority of the BnaPIPs and BnaTIPs was down-regulated in the roots. However, the BnaNIPs were up-regulated. In addition, the BnaCnn_random.PIP1;4b, BnaPIP2;4s, BnaC04.TIP4;1a, BnaAnn_random.TIP1;1b, and BnaNIP5;1s (except for BnaA07.NIP5;1c and BnaC06.NIP5;1c) exhibited obvious differences at low B between B-efficient and B-inefficient cultivars. These results will help us to understand boron homeostasis in B. napus.